Controlled supramolecular structure of guanosine monophosphate in the interlayer space of layered double hydroxide - Gwak, Gyeong-Hyeon; Kocsis, Istvan; Legrand, Yves-Marie; Barboiu, Mihail; Oh, Jae-Min (Beilstein Journal of Nanotechnology, 2016)
Guanosine monophosphates (GMPs) were intercalated into the interlayer space of layered double hydroxides (LDHs) and the molecular arrangement of GMP was controlled in LDHs. The intercalation conditions such as GMP/LDH molar ratio and reaction temperature were systematically adjusted. When the GMP/LDH molar ratio was 1:2, which corresponds to the charge balance between positive LDH sheets and GMP anions, GMP molecules were well-intercalated to LDH. At high temperature (100 and 80 °C), a single GMP molecule existed separately in the LDH interlayer. On the other hand, at lower temperature (20, 40 and 60 °C), GMPs tended to form ribbon-type supramolecular assemblies. Differential scanning calorimetry showed that the ribbon-type GMP assembly had an intermolecular interaction energy of ≈101 kJ/mol, which corresponds to a double hydrogen bond between guanosine molecules. Once stabilized, the interlayer GMP orientations, single molecular and ribbon phase, were successfully converted to the other phase by adjusting the external environment by stoichiometry or temperature control.
Keywords: guanosine monophosphate; hydrogen bond; layered double hydroxide; ribbon structure; supramolecular assembly